El sector agrícola y los procesos de inserción internacional latinoamericanos - Cuadra Carrasco, Gabriela (2008)
This paper analyzes the effects of the liberalization and/or exclusion of the agricultural sector in the integration processes in which are immersed the Latin American Countries from the comparison of four different ways from liberalization. The central objective consists of determining if it is necessary that this sector receives a special treatment in comparison with the rest of economic sectors, or if the complete liberalization is more/less favorable than the exclusion of the agriculture in the integration processes. We used a static CGE model, multisectorial, multicountry of short and long term that has a predominantly agricultural aggregation. Between the main results we found that although the four types of liberalization generate positive results in the Latin American economies; for Peru, Venezuela, Ecuador-Bolivia, Argentina and Uruguay the multilateral strategy that excludes the agricultural sector generates greater benefits than the net tariff liberalization. Despite if we compare the tariff liberalization versus the total liberalization (one that includes export subsidies elimination and band of prices), all the countries with exception of Peru and Venezuela register greater benefits with the total liberalization.